1999
DOI: 10.1046/j.1439-0450.1999.00248.x
|View full text |Cite
|
Sign up to set email alerts
|

Intranuclear Inclusions in Cells Infected with Newcastle Disease Virus

Abstract: Cells infected by Newcastle Disease Virus were observed to contain both intracytoplasmic and intranuclear inclusion bodies. Ultrastructurally, they consisted of twisted strands of about 18-20 nm diameter resembling nucleocapsids. The presence of these inclusions was detected irrespective of host cell or pathogenicity of the virus. In immunofluorescence and immunogold labelling experiments, these structures were tagged by an anti-P protein monoclonal antibody. In summary, we show that intracytoplasmic and intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
(28 reference statements)
1
6
0
Order By: Relevance
“…The presence of intracytoplasmatic and intranuclear inclusions, surrounded by a membrane and containing viral nucleocapsid are in accordance with other authors who used the resin embedding technique (Mannl et al, 1987;Granzow et al, 1999;Jacobson et al, 2001). …”
Section: Discussionsupporting
confidence: 90%
“…The presence of intracytoplasmatic and intranuclear inclusions, surrounded by a membrane and containing viral nucleocapsid are in accordance with other authors who used the resin embedding technique (Mannl et al, 1987;Granzow et al, 1999;Jacobson et al, 2001). …”
Section: Discussionsupporting
confidence: 90%
“…In contrast to our novel isolates, budding results in filamentous particles that later transform to a spherical shape. Moreover, neither orthomyxoviruses nor paramyxoviruses show the prominent circular RNP structure associated with the inner side of the plasma membrane at budding sites (Dubois-Dalcq et al 1984;King et al 2012 Granzow et al 1999;King et al 2012) that was not observed in cells infected with our isolates. In addition, while orthomyxovirus RNP strands were observed as 10-12 nm filamentous structures, paramyxovirus RNP was 18 nm thick and tubular, but distinctly thinner than the RNP strands in our isolates with a diameter of 28-32 nm.…”
Section: Discussionmentioning
confidence: 63%
“…After onset of cytopathogenic alterations, the monolayers were fixed and processed for electron microscopy as described by Granzow et al . (, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The specificity of the reaction in the immunofluorescence test is verified by the fact that foci of infected cells are clearly distinguishable from surrounding uninfected cells or from cells in uninfected control cups, respectively. As known for paramyxoviruses, antigen seems to be present predominantly in the cytoplasm, but can also appear in some of the nuclei, described as intranuclear inclusion bodies by Granzow et al (1999).…”
Section: Titre [Log2]mentioning
confidence: 98%